CONTENT OF ISLAMIC EDUCATION FOUND IN AL-QUR’AN SURAH AR-RAHMAN - Ali Fauzi (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2019)
In Al-Qur’an surah Ar-Rahman we find the content of Islamic education which consists of the education of Faith (Akidah), Morality (Akhlak), Islamic Law (Fikih) and Islamic History (Tarikh). However, many moslems just read it, do not know it and do not try to analyze it. Therefore, the researcher chooses the title “Content of Islamic Education Found in Al-Qur’an Surah Ar-Rahman,” and formulates the problem, how is the content of Islamic Education Found in Al-Qur’an surah Ar-Rahman?. The objective of the research is to describe the content of Islamic education found in Al-Qur’an Surah Ar-Rahman. It is hoped that this research will be useful for all. The approach of the research is phenomenological approach and the instrument of analysis is hermeneutics to interpret the facts, cause and effect based on the available phenomena. The research is qualitative research in form of content analysis and the method of research is descriptive-text-analysis. The data is taken from the words, phrases, sentences and verses found in the Holy book Al-Qur’an surah Ar-Rahman. The procedure of research is preparation, data collection, and finalization. The researcher then analyzes the data by the way of reducing data, presenting data and concluding data. He also validates them in order that the data he collects are really valid. The researcher then describes his finding data about the content of Islamic education in the Holy Al-Qur’an surah Ar-Rahman, consisting of the content of Faith (akidah), Morality (akhlak), Islamic Law (Fiqih) and Islamic History (tarikh). The discussion of Islamic education is done deeply and seen from many perspectives. The researcher concludes that in Al-Qur’an surah Ar-Rahman he finds Islamic education mentioned above. He, in this case, suggests the readers in order to read Al-Qur’an and to learn the content more and to try to analyze with the hope that they will get more understanding about it.